The Effect of Early Clinical Exposure on the Secondsemester Medical Students` Attitude toward Medical Profession - Habibeh Ahmadipour; Mohammad Javad Zahedi; Seyed Ali Mohammad Arabzadeh (Kerman University of Medical Sciences, 2012)
Background & Objectives: Even so much of the knowledge and skills of medical students is aquiered during clinical course in many educational systems students are kept away from clinical setting during their first academic years Methods: This study was an interventional study carried out by Educational Development Office in the school of Medicine in 2009 All Second semester students were selected through census method Students attitudes towards medical profession were evaluated using a questionnaire The validity of the questionnaire confirmed by a number of experts and its reliability was determined using Cronbachs Alpha 0 65 Early clinical exposure course was held for subjects and within two weeks after the course they were asked to complete the questionnaire again Each question was rated using Likert scale and mean scores of each student before and after the intervention were calculated and compared by using paired ttest Results: From 85 students 62 ones completed the questionnaire before and after the course From all 36 ones (58 %) were female and 26 ones (42 %) were male Mean age of students was 1912(± 073) years and their mean average of the first semester was 1624(± 11) There was no significant difference between the students attitude toward medical profession before and after the course Conclusion: Although the present study couldnt detect significant change in students attitude toward medical profession the results of other studies show that early clinical exposure provides an opportunity for the students to learn subjects practically and beyond mere theory